Analysis The Analysis of the Effect of Slice Thickness of Phantom on Image Quality of CT Scan at RSUD Bali Mandara - Hutami, Ida Ayu Putu Aristia; Sutapa, Gusti Ngurah; Paramarta, Ida Bagus Alit (BULETIN FISIKA; Vol 22 No 2 (2021): BULETIN FISIKA August Edition, 2021)
It has been investigated the effect of slice thickness on image quality with the Contrast to Noise Ratio (CNR) parameter method using a Toshiba (TOS) phantom. The variations in the slice thickness used were 1, 2, 3, 4, 6 and 8 mm. The X-ray tube voltage and the X-ray current time used were 80 kV, and 100 mAs, which following the patient head examination protocol. The analysis of the effect of slice thickness on CNR values is determined with a simple regression test with an exponential curve.. The test results showed that variations in slice thickness affect CNR values, where the greater the slice thickness then the CNR value would be higher and better the image quality.